1960
DOI: 10.1029/jz065i002p00771
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radiation in the lower Van Allen belt

Abstract: In the first of a series of experiments, an instrument package of eight Geiger counters, shielded and collimated in various ways, was carried aloft and released by an Atlas ICBM; its trajectory passed into the lower Van Allen radiation belt. Since there are variations in altitude at the isocount contours of the belt at several latitudes, the trajectory achieved its deepest penetration into the radiation belt somewhat after reaching its maximum height of 990 km (Fig. 1). Of the eight counters, two with relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1960
1960
1964
1964

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There seems to be no need for the proton spectrum to change with altitude to explain any of the measurements. The energy spectrum of the electrons in the inner zone has been measured by Holly and Johnson [1960]. It is moderately similar to the neutron /• decay spectrum.…”
Section: The 1xteutron Flux In Spacementioning
confidence: 88%
“…There seems to be no need for the proton spectrum to change with altitude to explain any of the measurements. The energy spectrum of the electrons in the inner zone has been measured by Holly and Johnson [1960]. It is moderately similar to the neutron /• decay spectrum.…”
Section: The 1xteutron Flux In Spacementioning
confidence: 88%
“…13). A measurement, employing shielded Geiger tubes, at ~ 1100 km along lines of force extending to ~ 1.3 --1.6R [Holly and Johnson, 1960;Holly, 1960] found an electron energy spectrum similar to the higher altitude spectrum (Walt) above ~ 200 kev (Fig. 13).…”
Section: Comparison •Riti-i Observationsmentioning
confidence: 92%
“…The Van Allen radiation is a belt of energetic particles trapped in the earth's magnetic field. This belt has been shown to consist of two components: (1) a hard proton component (the proton belt) centered at about 104 km from the earth's magnetic axis [Freden and White, 1959; Fan, Meyer, and Simpson, 1960; McIlwain, Resuits from Explorer IV, presented at NASA seminar on Van Allen radiation, March 26-27, 1959, unpublished]; and (2) an electron component which extends through the region occupied by the proton belt [Holly and Johnson, 1960]. The work of Vernov, Chudakov, Vakulov, and Logachev [1959] and Walt, Chase, Cladis, Imho•, and K•echt [1960] has shown that the penetrating component of the outer belt is composed of electrons.…”
Section: Introductionmentioning
confidence: 99%